The role of housing finance policies in reducing the housing crisis in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Finance is considered as an important and essential element when developing any housing policy which has a basic role creation of channels and effective means of saving money for individuals and institutions involved in the construction of housing units , and in particular that there is a deficit of residential dramatically in Iraq offset by a significant decline in the rates of construction housing and the accumulation of housing need in the coming years , the importance lies of the subject in creating mechanism for financing this sector and the impact of such a mechanism in solving the problem of the deficit number of housing units, through studying the experiences of some countries in the policies of housing finance to take advantage of those experiences in directing policies of housing finance in Iraq and of the Bank's real estate and housing fund.The research has come to the most important results represented the lack of an effective system of housing finance and the adoption of funding for the Bank of the real estate and housing fund is allocated by the state of the amounts of the Ministry of Finance has led to the decline and the weakness of the role of these institutions, so it was the most important recommendations is to propose mechanisms and to develop solutions to the problems faced by the lending institutions residential after diagnosis and that by taking advantage of the experiences of some countries in this area, and facilitate the entry of the private sector by encouraging private sector commercial banks to provide loans to citizens and encourage competition among them.